La Prueba de Conceptos Básicos de Boehm: adaptación y elaboración de baremos para Lima y Callao - Thorne, Cecilia (1987)
This study reports the translation and adaptation of the Boehm Test of Basic Concepts. In order to study the reliability and validity of the test, the adapted version was administered to 308 kindergarten and first grade children, of both sexes and different socioeconomic levels. The results indicate that the test has validity and re!iabilit in our milieu. In the Jast part of the paper, tables are presented with the percentage of children passing each item, as well as the percentile equiva!ents of raw scores by grade and socioeconomic level.